Changing diets and the transformation of the global food system - Vermeulen, Sonja J.; Park, Toby; Khoury, Colin K.; Béné, Christophe (Wiley, 2020)
An aspirational global food system is one that delivers across a suite of the Sustainable Development Goals (SDGs), including universal access to healthy diets, which can also codeliver on climate and environment SDGs. The literature has downplayed the relative contribution of dietary change to sustainable food systems. In this perspective article, we argue that the potential for positive transformational change in diets should not be underestimated, for two sets of reasons. First, the dynamism of diets over long‐term and, especially, recent history shows the potential for rapid and widespread change, including toward more diverse and healthier diets. Second, contemporary behavioral research demonstrates promising tactics to influence consumers’ dietary choices. Since the entire food system creates the circumstances of those choices, the most effective strategies to shift diets will involve multiple approaches that deliberately aim not just to influence consumers themselves but also to incentivize all actors in the food systems, taking into account multiple agendas and values. The effectiveness of actions will depend on the political economy at local, national, and global levels. Overall, there are reasons to be hopeful about the potential for accelerated global dietary change, given both historic trends and the growing suite of tools and approaches available.